Hypoglycemia in a resource-poor Nigerian environment: A cross-sectional study of knowledge of symptoms, causes, and self-management practices among ambulatory type 2 diabetic patients in South-East Nigeria - Gabriel Uche Pascal Iloh; Peace Ifeoma Collins (Wolters Kluwer Medknow Publications, 2017)
Background: Hypoglycemic emergencies are potentially life-threatening complication of diabetes management that predisposes the patients to higher risk of disability and premature death. As the impetus for the prevention of diabetes-related hypoglycemic endpoints grows, emphasis should also be focused on patients' knowledge of symptoms, causes, and self-management practices for hypoglycemia. Aim: The study was aimed at describing the knowledge of symptoms, causes, and self-management practices for hypoglycemia among ambulatory type 2 diabetic patients in Eastern Nigeria. Materials and Methods: A cross-sectional descriptive study was carried out on 145 type 2 diabetic Nigerians at a primary care clinic in Eastern Nigeria. Data on knowledge of symptoms, causes, and self-management practices for hypoglycemia were collected using pretested, structured, and researcher-administered questionnaire. Results: The age of the type 2 diabetic patients ranged from 32 to 78 years with mean age of 44 ± 10.2 years. There were 59 (40.7%) male and 86 (59.3%) female. Thirty-six (24.8%), 22.8%, and 29.0% had adequate knowledge of symptoms, causes, and self-management practices for hypoglycemia with the most common symptom, cause, and self-management practice being dizziness (69.7%), overdose of antidiabetic medications (91.0%), and taking drink containing glucose (67.6%), respectively. Educational level was significantly associated with adequate knowledge of symptoms (P = 0.039), causes (P = 0.02), and self-management practices (P = 0.016) for hypoglycemia. Conclusion: Knowledge of causes, symptoms, and self-management practices for hypoglycemia was inadequate. The most common symptom, cause, and self-management practice for hypoglycemia were dizziness, overdose of medications, and taking of drink containing glucose, respectively. Adequate knowledge of causes, symptoms, and self-management practices for hypoglycemia was associated with educational level. There is a need for hypoglycemic-oriented diabetes education, especially in resource-poor environment.